2018
DOI: 10.1016/j.jval.2018.04.573
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of Sofosbuvir/Velpatasvir in Genotype 1 Hepatitis C Infected Patients in Mexico

Abstract: ObjectiveS: To assess the cost-effectiveness of therapist guided Internet delivered cognitive behavioral therapy (i-CBT) compared to treatment as usual (TAU) in the management of functional abdominal pain disorders (FAPDs). MethOdS: Ninety children aged 8-12 years, with a diagnosis of irritable bowel syndrome, functional dyspepsia, or functional abdominal pain were randomized to either a treatment consisting of 10 weeks of therapist-guided i-CBT or TAU. The health outcome measure was Paediatric Quality of Life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In the probabilistic sensitivity analysis, all iterations demonstrated that both treatments had similar results and were thus regarded as promising treatments. Other studies have also highlighted the cost saving potential of both treatments in scenarios that were either similar or different from our base case [11][12][13] . Furthermore, both treatments enable notable response and are thus good choices.…”
mentioning
confidence: 71%
“…In the probabilistic sensitivity analysis, all iterations demonstrated that both treatments had similar results and were thus regarded as promising treatments. Other studies have also highlighted the cost saving potential of both treatments in scenarios that were either similar or different from our base case [11][12][13] . Furthermore, both treatments enable notable response and are thus good choices.…”
mentioning
confidence: 71%